Determinants of delayed childhood cancer care in low‐ and middle‐income countries: A systematic review. Issue 3 (29th December 2022) - Cotache‐Condor, Cesia; Kantety, Vinootna; Grimm, Andie; Williamson, Jahsarah; Landrum, Kelsey R; Schroeder, Kristin; Staton, Catherine; Majaliwa, Esther; Tang, Shenglan; Rice, Henry E.; Smith, Emily R.
Abstract: Early access to care is essential to improve survival rates for childhood cancer. This study evaluates the determinants of delays in childhood cancer care in low‐ and middle‐income countries (LMICs) through a systematic review of the literature. We proposed a novel Three‐Delay framework specific to childhood cancer in LMICs by summarizing 43 determinants and 24 risk factors of delayed cancer care from 95 studies. Traditional medicine, household income, lack of transportation, rural population, parental education, and travel distance influenced most domains of our framework. Our novel framework can be used as a policy tool toward improving cancer care and outcomes for children in LMICs.